(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article describes the method of using German-language songs in teaching German grammar. Songs help to achieve the best activation and assimilation of grammatical structures. The methodology for working with educational songs includes the following steps: familiarization with the grammatical material used in the text; explanation of grammatical material; consolidation of the introduced material; application of learned grammatical material; control of the level of proficiency in grammatical material. As an example, only some types of tasks that can be used in working with German-language song material are given. Their choice will depend on which particular grammatical phenomenon is needed study in class. Also important conditions are the functionality of tasks and their effectiveness.